Characteristics of sludge granulation and EPS production in development of stable partial nitrification. (May 2020) - Li, Xiangchen; Du, Rui; Peng, Yongzhen; Zhang, Qiong; Wang, Jincheng
Highlights: Nitrite accumulation ratio achieved 96.36% and 77.30% in SBR and AeUSB respectively. Secretion of EPS especially protein played an important role in granulation. Protein secondary structure of α -helices and 3-turn helices promoted granulation. Structure of micro-granules contributes to AOB-dominated nitrifying population. Aggregation of sludge benefited start-up and stability of partial nitrification. Abstract: In this study, sequencing batch reactor (SBR) and aerobic upflow sludge bed reactor (AeUSB) were used to investigate the effects of sludge granulation on establishing partial nitrification (PN) process and explore the potential mechanism. The particle size was positively related to the NO2 − -N accumulating performance, satisfactory nitrite accumulation rate (NAR) of 96.4% and 77.3% were obtained with the appearance of micro-granules in SBR and AeUSB after day 105 and 83, respectively. To our knowledge, it is the first report describing the importance of extracellular polymeric substances (EPS) content and components, such as aromatic protein-like substances, by-product-like substances and special protein secondary structures ( α -helices and 3-turn helices) for sludge granulation and even PN process. Quantitative microbial analysis suggested that ammonium oxidizing bacteria (AOB) predominated in nitrifying-bacterium in micro-granules system, guaranteeing a highly efficient PN process.